Algebra and coalgebra in computer science 4th International Conference, CALCO 2011, Winchester, UK, August 30 - September 2, 2011. Proceedings - Corradini, Andrea; Klin, Bartek; Cîrstea, Corina (Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 4th International Conference on Algebra and Coalgebra in Computer Science, CALCO 2011, held in Winchester, UK, in August/September 2011. The 21 full papers presented together with 4 invited talks were carefully reviewed and selected from 41 submissions. The papers report results of theoretical work on the mathematics of algebras and coalgebras, the way these results can support methods and techniques for software development, as well as experience with the transfer of the resulting technologies into industrial practice. They cover topics in the fields of abstract models and logics, specialized models and calculi, algebraic and coalgebraic semantics, and system specification and verification. The book also includes 6 papers from the CALCO-tools Workshop, colocated with CALCO 2011 and dedicated to tools based on algebraic and/or coalgebraic principles. 0